Clopidogrel response status assessed with Multiplate point-of-care analysis and the incidence and timing of stent thrombosis over six months following coronary stenting - Sibbing, Dirk; Morath, Tanja; Braun, Siegmund; Stegherr, Julia; Mehilli, Julinda; Vogt, Wolfgang; Schömig, Albert; Kastrati, Adnan; Beckerath, Nicolas von (Thrombosis and Haemostasis, 2010)
Clopidogrel low-responsiveness assessed with multiple electrode platelet aggregometry (MEA) has been shown to be a strong and independent predictor of early stent thrombosis (ST) after coronary stenting. The relation of clopidogrel response status, as assessed with MEA, with incidence and timing of ST during an extended follow-up period has never been reported. Here, we report the six-month follow-up results of a prospective trial assessing clopidogrel responsiveness with MEA in patients undergoing percutaneous coronary intervention (PCI). A total of 1,608 consecutive patients with planned drug-eluting stent placement were enrolled in this study. Before PCI patients uniformly received 600 mg clopidogrel and blood was taken directly before PCI to measure ADP-induced platelet aggregation with MEA. The upper quin-tile (20%) of patients according to MEA measurements (n=323) was defined as clopidogrel low responders. Compared with normal responders (n=1,285), the cumulative incidence of definite ST within six months was significantly higher in low responders [2.5% vs. 0.4%; OR 6.5; 95% CI, 2.4–17.0; P<0.001]. The combined incidence of definite or probable ST was higher as well in low vs. normal responders [4.1% vs. 0.7%; OR 5.8; 95% CI, 2.8–12.3; P<0.0001]. A significant inverse correlation of MEA values and the timing of definite or probable ST (in days) was observed (Spearman coefficient = –0.45; P=0.04) with events occurring earlier in the low-responder group. MEA measurements are highly predictive for the occurrence of ST during the first six months following coronary stenting. In the majority of clopidogrel low responders suffering ST, the ischaemic event occurs early in the course after the procedure.
Keywords: Clopidogrel; stent thrombosis; platelet aggregation; whole blood aggregometry